Testing a chain mediation model of effort-reward imbalance, Confucian values, job satisfaction, and intention to quit among Chinese vocational education teachers - Wang, Guantao; Shi, Jinyu (Frontiers in Psychology, 2024)
Context: This research delves into the significant impact of Confucian Values on the societal fabric of China, particularly in the realm of early childhood education. In this setting, these principles are instrumental in guiding both educators and students. The study employs the Culture-Value Structure (CVS) model to dissect the intricate dynamics between Confucian Values, the Effort-Reward Imbalance (ERI), educators' job satisfaction, and their inclination towards leaving the profession. Teachers in early education, who are often regarded as moral guides, play a pivotal role in the ethical and social upbringing of children. The ERI model, proposed by Siegrist, serves as a tool to comprehend the stress experienced when there is a disproportion between efforts and rewards. This study delves into how ERI correlates with job satisfaction among early education teachers, with a focus on the modifying effect of Confucian values. Additionally, it examines the potential role of job satisfaction in mediating the relationship between ERI and the tendency to consider leaving the job. The research illuminates the complex interrelation of cultural values, occupational stress, job contentment, and career decision-making in the context of early childhood education in China. Methodology: The research involved a group of 332 early education teachers from diverse Chinese institutions. Through thorough statistical analysis, the study validated the model's effectiveness, notably indicating a substantial direct impact of ERI on the Intention to Quit. Findings: The investigation pinpointed Factors I (Integrity), II (Confucian Ethos), and IV (Moderation) as key determinants of job satisfaction. Notably, an increase in job satisfaction was found to inversely relate to the likelihood of leaving the profession, implying it could lessen the propensity to resign. The research applied a Chain Mediation Model to elucidate the influence of ERI on the decision to quit, mediated by various factors.The findings highlight the complex interaction of elements influencing teachers' decisions to leave, showcasing the utility of sophisticated statistical methodologies in decoding complex social dynamics.